Measuring Students’ Aptitude in Writing Makassar Lontara’ Script Using Card Letters Media - Hamriani Hamriani; Usman Usman; Denok Sunarsi; Afzal Sayed Munna (Universitas Negeri Makassar, 2022)
The purpose of this study is to compare the capacity of students to write Makassar Lontara script before and after utilizing the letter card medium. This investigation used three steps: pre-test, therapy, and post-test. This study included fifty public Yunior High School students in the Makassar city, South Sulawesi, Indonesia. Participatory observation, testing, and interviews were employed to obtain data for this study. Data description, average similarity test, and analysis requirement test are among the data analysis approaches employed. The findings revealed that learning through the medium of letter cards was more successful. The post-test analysis demonstrates the usefulness of using the letter card medium. Using Makassar Lontara's letter card medium, the level of achievement is higher than the pre-test result. Furthermore, when employing letter card media in the learning process, pupils are more active than when not using the media. Teachers of local content subjects are encouraged to use learning methods and enjoyable media for students to achieve more effective learning. The Makassar Lontara' letter card media is one of the methods employed. Because the media can contribute significantly to both the learning process and the desired outcomes, it is intended that by using the Makassar Lontara' letter card learning media, students will be more interested in and motivated to study local content themes that have previously been intimidating to them. Further research is needed to increase the quality of learning, and it is hoped that future researchers will address any flaws found in this study.